2021
DOI: 10.3389/fcimb.2021.728933
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Potential of Oral Microbiota as a Screening Tool for Oral Squamous Cell Carcinomas

Abstract: IntroductionThe oral squamous cell carcinoma (OSCC) is detrimental to patients’ physical and mental health. The prognosis of OSCC depends on the early diagnosis of OSCC in large populations.ObjectivesHere, the present study aimed to develop an early diagnostic model based on the relationship between OSCC and oral microbiota.MethodsOverall, 164 samples were collected from 47 OSCC patients and 48 healthy individuals as controls, including saliva, subgingival plaque, the tumor surface, the control side (healthy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 51 publications
1
54
0
Order By: Relevance
“… 87 , 88 Microbiome sequencing was used to evaluate the bacterial communities associated with OSCC, and it was found that the diversity and relative abundance of bacteria in the saliva of OSCC patients changed significantly. 74 , 89 When used as a diagnostic marker, oral bacteria were found to have 80% sensitivity and 83% specificity between the case group and the control group. 74 …”
Section: Oral Bacteria and Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“… 87 , 88 Microbiome sequencing was used to evaluate the bacterial communities associated with OSCC, and it was found that the diversity and relative abundance of bacteria in the saliva of OSCC patients changed significantly. 74 , 89 When used as a diagnostic marker, oral bacteria were found to have 80% sensitivity and 83% specificity between the case group and the control group. 74 …”
Section: Oral Bacteria and Cancersmentioning
confidence: 99%
“… 74 , 89 When used as a diagnostic marker, oral bacteria were found to have 80% sensitivity and 83% specificity between the case group and the control group. 74 …”
Section: Oral Bacteria and Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a wide heterogeneity was observed which made it impossible to perform an advanced statistical analysis. Eight studies were case–control [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], two were cohort studies [ 35 , 36 ], and one was a cross-sectional cohort study [ 37 ]. Of the eleven studies, five were from Taiwan [ 30 , 34 , 35 , 36 , 37 ], three were from China [ 28 , 29 , 32 ], one was from the USA [ 27 ], one was from Sudan [ 31 ], and one was from Japan [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous methods have either assessed biomolecules from the human side (e.g. CD44 protein [39] or RNA – 6 markers that include interleukins IL-1Beta, IL-8, OAZ1SAT1S100P, and DUSP1 [40] or difference in species with 16S rRNA gene sequencing and metagenomics [41] [42], but their results are less promising, and while they have reported discovery results, they have not been validated in independent cohorts. Large independent prospective studies are required to advance adoption of the new adjunctive technologies in clinical and eventually in home-based testing settings.…”
Section: Discussionmentioning
confidence: 99%